Ultra-stable Y-type molecular sieve as well as preparation method and application thereof
By introducing Fe atoms in the Y-type molecular sieve synthesis process and controlling the growth of crystal nuclei, combining hydrothermal and pickling treatment, the problems of complexity of existing modification methods and insufficient catalytic performance are solved, and a Y-type molecular sieve with high pore volume and excellent catalytic performance are achieved.
Patent Information
- Application Number
- CN202311257268.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-26
AI Technical Summary
The existing Y-type molecular sieve modification methods are complex, long time, and difficult to improve catalytic performance, especially in terms of pore structure and reaction performance.
By introducing Fe atoms into the molecular sieve backbone, nucleation particles containing unstable "sites" are formed, and nucleation and nucleation growth are controlled through the "two-step method" during the synthesis process, combining hydrothermal treatment and pickling treatment to promote the generation of mesoporous.
The total pore volume and mesoporous ratio of the Y-type molecular sieve is significantly improved, its adsorption, diffusion and form selectivity are improved, thereby improving the activity and selectivity of the hydrocracking catalyst.
Smart Images

Figure CN119706865A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of Y-type molecular sieve preparation, and specifically relates to an ultra-stable Y-type molecular sieve and a preparation method and application thereof. Background Art
[0002] Hydrocracking catalyst is a bifunctional catalyst, and Y-type molecular sieve is widely used in hydrocracking catalyst as the main cracking component, and its catalytic performance can be improved by the modification of molecular sieve. At present, there are many modification methods for Y-type molecular sieve, but it is basically conventional post-processing modification, and the influence of this method on the properties of Y molecular sieve is limited, and other atoms are difficult to enter into the Y-type molecular sieve framework. For example, CN104828839A discloses a preparation method of a small-grained Y-type molecular sieve, which processes small-grained NaY molecular sieve with alkaline solution, and the obtained Y molecular sieve is dealuminated and silicon-filled with ammonium fluorosilicate aqueous solution, and hydrothermal treatment further dealuminates to increase the framework silicon-aluminum ratio. However, the method has the problems of complex modification process, long modification time, and the molecular sieve needs to undergo ammonium exchange, ammonium fluorosilicate modification and hydrothermal treatment three processes, resulting in a low product yield, which is not conducive to large-scale industrial application.
[0003] Microporous molecular sieves have limited pore size, and are affected by the pore structure during the reaction, which limits the reaction performance. Therefore, it is necessary to synthesize a stable Y-type molecular sieve with a multi-level pore structure to remove the diffusion limitation of macromolecular reactants.
[0004] In summary, in the process of Y-type zeolite synthesis, constructing heteroatom-modified Y-type zeolite and then regulating the relevant properties of the zeolite can greatly simplify the modification steps of Y-type zeolite, thereby preparing a hydrocracking catalyst with better performance, which is an urgent problem to be solved. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides an ultra-stable Y-type molecular sieve and a preparation method and application thereof. The ultra-stable Y-type molecular sieve of the present invention is particularly suitable as an acid component of a hydrocracking catalyst, which is beneficial to improving the activity and selectivity of the catalyst.
[0006] The first aspect of the present invention provides a method for preparing an ultrastable Y-type molecular sieve, comprising the following steps:
[0007] (1) mixing a first aluminum source, a first alkali source, a first Fe source, a first silicon source and water to obtain a Fe-containing Y molecular sieve guide;
[0008] (2) mixing a second aluminum source, a second silicon source, a second Fe source, a second alkali source, water and the guide body of step (1) to obtain a gel;
[0009] (3) crystallizing the gel of step (2);
[0010] (4) The crystallized product obtained in step (3) is subjected to ammonium exchange, hydrothermal treatment, and acid washing to obtain an ultra-stable Y-type molecular sieve, namely, USY molecular sieve.
[0011] Furthermore, in step (1), the method for preparing the Fe-containing Y molecular sieve guide body preferably comprises: mixing a first aluminum source, a first alkali source, a first Fe source, a first silicon source and water, and letting it stand to obtain the Fe-containing Y molecular sieve guide body. The first Fe source is selected from at least one of ferric chloride, ferric sulfate and ferric nitrate. The first aluminum source is selected from at least one of sodium metaaluminate and aluminum sulfate, the first alkali source is selected from at least one of NaOH and KOH, and the first silicon source is selected from at least one of silica sol and water glass.
[0012] Furthermore, in step (1), in the method for preparing an Fe-containing Y molecular sieve guide, the first aluminum source is calculated as Al2O3, the first alkali source is calculated as NaOH, the first Fe source is calculated as Fe2O3, and the first silicon source is calculated as SiO2, and the molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O is 1:(11-42):(0.05-10.0):(5-25):(180-450), preferably 1:(15-35):(0.05-8.0):(5-18):(180-400).
[0013] Furthermore, in the preparation method of the Fe-containing Y molecular sieve guide in step (1), preferably, the standing temperature is 10 to 50° C. and the standing time is 15 to 35 hours.
[0014] Furthermore, in step (1), in the method for preparing the Fe-containing Y molecular sieve guide body, preferably, after the first aluminum source and the first alkali source are mixed and dissolved with water, the first Fe source and the first silicon source are added in sequence, the mixture is mixed evenly, and the mixture is allowed to stand to obtain the Fe-containing Y molecular sieve guide body.
[0015] Furthermore, in step (2), the matrix mixed solution is a second aluminum source, a second silicon source, a second Fe source, a second alkali source and water.
[0016] Furthermore, in step (2), the second Fe source is selected from at least one of ferric chloride, ferric sulfate, and ferric nitrate. The second aluminum source is selected from at least one of sodium metaaluminate and aluminum sulfate. The second alkali source is selected from at least one of NaOH and KOH. The second silicon source is selected from at least one of silica sol and water glass.
[0017] Furthermore, in step (2), in the matrix mixed solution, the second aluminum source is calculated as Al2O3, the second alkali source is calculated as NaOH, the second Fe source is calculated as Fe2O3, and the second silicon source is calculated as SiO2, and the molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O is 1:(1.5~15.0):(0.05~12.0):(1.5~12.0):(80~400), preferably 1:(1.5~10.0):(0.05~8.0):(1.5~8.0):(80~350).
[0018] Furthermore, in step (2), the amount of Fe-containing Y molecular sieve guide added is 10.0% to 45.0% of the total mass of the matrix mixed solution.
[0019] Furthermore, in step (2), the second Fe source is introduced into the reaction system in the form of a second Fe source feed, and the second Fe source feed is preferably prepared in at least one of the following ways:
[0020] a. at least part of the second Fe source and at least part of the second silicon source are used to form a second Fe source feed,
[0021] b. at least part of the second Fe source and at least part of the second aluminum source are used to form a second Fe source feed,
[0022] c. At least part of the second Fe source, at least part of the second aluminum source and at least part of the second silicon source are used to make a second Fe source feed.
[0023] Further, in step (2), the mass content of Fe (in terms of oxide) in the second Fe source feed is 0.5% to 12.0%, preferably 4.0% to 12.0%. Preferably, the second Fe source feed is subjected to ultrasonic treatment and then to a standing process (preferably, the standing time is 1 to 48 hours, preferably 12 to 24 hours), and then introduced into the reaction system. Preferably, the ultrasonic treatment conditions are as follows: temperature 20 to 80° C., preferably 20 to 60° C., ultrasonic frequency 20 to 50 kHz, time 1 to 8 hours, preferably 1 to 4 hours.
[0024] Furthermore, in step (2), the matrix mixture (second aluminum source, second silicon source, second Fe source, second alkali source and water) is mixed with the guide body of step (1) to obtain a gel. Specifically, the second alkali source and the second silicon source are mixed with water and then the guide body, the second Fe source and the second aluminum source obtained in step (1) are added in sequence and mixed to obtain a gel.
[0025] Furthermore, in step (2), the matrix mixture (second aluminum source, second silicon source, second Fe source, second alkali source and water) is mixed with the guide body of step (1) to obtain a gel. Preferably, the second Fe source is introduced into the reaction system in the form of a second Fe source feed. Specifically, the second alkali source and the remaining second silicon source are mixed with water, and then the guide body, the second Fe source feed, and the remaining second aluminum source obtained in step (1) are added in sequence and mixed to obtain a gel, wherein the remaining second silicon source or the remaining second aluminum source refers to the remaining second silicon source or the second aluminum source other than the second silicon source or the second aluminum source used in preparing the second B source feed.
[0026] Furthermore, in step (3), the crystallization adopts three-stage temperature rising crystallization, the primary crystallization temperature is 30-40° C., the secondary crystallization temperature is 30-35° C. higher than the primary temperature, the tertiary crystallization temperature is 25-50° C. higher than the secondary temperature, and the highest temperature does not exceed 110° C. The crystallization time of each stage is 12-36 hours, preferably 15-24 hours.
[0027] Furthermore, in step (4), the ammonium exchange is a conventional ammonium exchange. The ammonium salt used may be one or more of ammonium chloride, ammonium nitrate, and ammonium sulfate, wherein the concentration of the ammonium salt solution is 0.1 to 3.0 mol / L, and the pH value is 1.0 to 7.0, preferably 2.0 to 7.0. The ammonium exchange temperature is 30 to 90° C., preferably 40 to 60° C., and the number of ammonium exchanges is 1 to 5 times. The solid-liquid volume ratio of each ammonium exchange is 1:10 to 1:20, and the treatment time of each ammonium exchange is 3 to 6 hours.
[0028] Furthermore, in step (4), the hydrothermal treatment is performed 1 to 3 times, preferably 2 times, and the conditions for each hydrothermal treatment are as follows: the temperature is 500 to 650° C., the treatment time is 1 to 6 hours under the condition of 100% steam treatment. The steam treatment can be a closed steam treatment or a flowing steam treatment, preferably a flowing steam treatment.
[0029] Furthermore, in step (4), the acid in the acid solution used for pickling treatment is selected from at least one of citric acid, oxalic acid, and tartaric acid, and the acid solution concentration is 0.1 to 3.0 mol / L. The solid-liquid ratio in the pickling treatment is 1.0 g: (5.0 to 20.0) mL, the temperature of the pickling treatment is 30.0 to 95.0° C., and the time of the pickling treatment is 1 to 6 hours.
[0030] The second aspect of the present invention provides an ultrastable Y-type molecular sieve prepared by the above method.
[0031] Furthermore, the properties of the molecular sieve are as follows: the mesopore volume accounts for 35% to 65% of the total pore volume of the molecular sieve, preferably 35% to 55%.
[0032] Furthermore, the properties of the molecular sieve are as follows: the specific surface area is 550-655m 2 / g, and the pore volume is 0.42~0.48mL / g.
[0033] Furthermore, in the molecular sieve, the average crystallite size is 0.4 to 1.2 μm, preferably 400 to 600 nm.
[0034] Furthermore, the unit cell constant of the molecular sieve is
[0035] Furthermore, in the molecular sieve, the SiO2 / Al2O3 molar ratio is 12.0 to 24.0, preferably 17.0 to 20.0.
[0036] The third aspect of the present invention provides the use of the above molecular sieve in a hydrocracking catalyst.
[0037] Furthermore, the application is to use USY molecular sieve in the manufacture of flexible hydrocracking catalyst.
[0038] Furthermore, the hydrocracking catalyst comprises USY molecular sieve and hydrogenation active metal components. The hydrogenation active metal is preferably a metal of Group VIB and Group VIII, and more preferably molybdenum, tungsten and nickel. Based on the weight of the catalyst, the content of USY molecular sieve is 15.0%-45.0%, the content of molybdenum in terms of oxide is 3.0%-12.0%, the content of tungsten in terms of oxide is 10.0%-18.0%, and the content of nickel in terms of oxide is 2.0%-8.0%.
[0039] Furthermore, the hydrocracking catalyst also includes aluminum oxide, and the content of aluminum oxide is 40%-70% based on the weight of the catalyst.
[0040] Furthermore, the hydrocracking catalyst is particularly suitable for catalytic cracking of polycyclic macromolecules, the raw material can be vacuum wax oil, the initial distillation point is 350-370°C, the final distillation point is 515-540°C, and the main target products are heavy naphtha and jet fuel.
[0041] Furthermore, the hydrogenation catalyst may be presulfurized according to conventional methods in the art before use. The presulfurization method may be: presulfurizing the hydrogenation catalyst with sulfur, hydrogen sulfide or sulfur-containing raw materials at 165-320° C. in the presence of hydrogen.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] Conventional Y molecular sieve framework is relatively stable, even if the number of mesopores formed by hydrothermal treatment is still very limited. The inventors have found through research that the introduction of Fe atoms into the framework of the molecular sieve will be more conducive to the framework distortion of the heteroatom-modified Y molecular sieve, because the bond length of the Fe-O bond is greater than the Al-O bond length, and the stability of the molecular sieve framework will be weakened. In addition, the hydrothermal treatment process and the acid washing process are combined to wash away the non-framework iron and aluminum in the molecular sieve pores, thereby further enriching the proportion of mesopores in the molecular sieve, and also improving the comprehensive performance of the Y-type molecular sieve.
[0044] The Fe modified Y molecular sieve of the present invention is different from the Y molecular sieve modified by post-treatment in the past, but the Y molecular sieve is synthesized in a guide body and firstly Fe is introduced to form a crystal nucleus particle containing an unstable "site", and then Fe is introduced again in the matrix solution of the synthetic Y molecular sieve, and by the "two-step method" of the present invention, both the nucleation process and the crystal nucleus growth process are controlled, and the heteroatom Fe has a more obvious effect on the modification of the Y molecular sieve, and the inherent properties of the Fe atom can be fully utilized to promote the instability of the skeleton, and finally combined with the dealumination of the hydrothermal process, the generation of mesopores in the Y molecular sieve can be greatly promoted, and the proportion of mesopores in the total pore volume of the Y molecular sieve can be greatly increased. When the Y molecular sieve is used for a hydrocracking catalyst, the adsorption, diffusivity and shape selectivity of the molecular sieve are better, and the reaction activity and selectivity can be improved.
[0045] The method of the present invention can obtain a USY type molecular sieve with a high silicon-aluminum ratio, a large specific surface area and a large pore volume, and the molecular sieve can be used as a cracking component of a hydrocracking catalyst. The flexible hydrocracking catalyst prepared therefrom has significantly improved activity and selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is the XRD pattern of the USY molecular sieve obtained in Example 1. DETAILED DESCRIPTION
[0047] The technical solutions and effects of the present invention are further described below in conjunction with embodiments, but are not limited to the following embodiments.
[0048] In the present invention, a physical adsorption instrument is used to measure the pore volume, pore distribution, most probable pore size and specific surface area of the molecular sieve by nitrogen low temperature adsorption and desorption method, wherein the pore volume and pore size distribution are obtained by the BJH method, and the specific surface area is obtained by the BET method.
[0049] In the present invention, an X-ray diffractometer (XRD) is used to determine the phase and unit cell constant of the molecular sieve, and the Breck-Flanigen formula is used to calculate the silicon-aluminum ratio of the molecular sieve. The experimental conditions are: CuKα radiation, tube voltage 40kv, tube current 40mA.
[0050] In the present invention, a scanning electron microscope is used to statistically analyze the particle size distribution of the molecular sieve.
[0051] In the present invention, the distillation range of heavy naphtha is 65-177°C, and the distillation range of aviation kerosene is 177-260°C.
[0052] In the present invention, the yield of heavy naphtha refers to the mass ratio of heavy naphtha to fresh hydrocracking feedstock (vacuum gas oil) in the hydrocracking product, and the yield of jet fuel refers to the mass ratio of jet fuel to fresh hydrocracking feedstock in the hydrocracking product.
[0053] Example 1
[0054] (1) Preparation of Fe-containing Y molecular sieve guide body: The first Fe source is ferric chloride, the first aluminum source is sodium aluminate, the first alkali source is NaOH, and the first silicon source is silica sol. After the first aluminum source and the first alkali source are mixed and dissolved in water, the first Fe source and the first silicon source are added in sequence, mixed evenly, and allowed to stand to obtain the Fe-containing Y molecular sieve guide body. Among them, the first aluminum source is calculated as Al2O3, the first alkali source is calculated as NaOH, the first Fe source is calculated as Fe2O3, and the first silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the feed is 1:32:0.80:14:320. The standing temperature is 45°C and the standing time is 18 hours.
[0055] (2) Prepare a matrix mixed solution; in the matrix mixed solution, the second Fe source is ferric chloride, the second aluminum source is sodium aluminate and aluminum sulfate (the molar ratio of sodium aluminate and aluminum sulfate is 1:0.55), the second alkali source is selected from NaOH, and the second silicon source is water glass. In the matrix solution, the second aluminum source is calculated as Al2O3, the second alkali source is calculated as NaOH, the second Fe source is calculated as Fe2O3, and the second silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the feed is 1:5.5:0.40:5.4:140. The amount of the Fe-containing Y molecular sieve guide added in step (1) is 16.0% of the total mass of the matrix mixed solution. The second Fe source is dissolved in the second aluminum source sodium aluminate aqueous solution, wherein the mass content of Fe (in terms of oxide) is 6.0%. After ultrasonic treatment (frequency 35kHz) for 5 hours and a standing process, the standing time is 20 hours, to obtain the second Fe source feed. The second alkali source and the second silicon source are mixed with the remaining water, and then the guide body obtained in step (1), the second Fe source feed, and the second aluminum source aluminum sulfate are added in sequence and mixed evenly to obtain a gel.
[0056] (3) The gel obtained in step (2) is crystallized; the crystallization adopts three-stage temperature rising crystallization, the first stage crystallization temperature is 30° C., the second stage crystallization temperature is 65° C., and the third stage crystallization temperature is 100° C. The crystallization time of each stage is 20 hours.
[0057] (4) The crystallized product obtained in step (3) was subjected to ammonium exchange, hydrothermal treatment, and acid washing to obtain USY molecular sieve (XRD Figure 1 ,Depend on Figure 1 It can be seen that there is a diffraction peak of Y-type molecular sieve). The ammonium exchange is a conventional ammonium exchange. The ammonium salt used is ammonium nitrate, wherein the concentration of the ammonium salt solution is 0.1 mol / L and the pH value is 6.7. The ammonium exchange temperature is 60°C, and the number of ammonium exchanges is 2 times. The solid-liquid volume ratio of each ammonium exchange is 1:10, and the treatment time of each ammonium exchange is 6 hours. The hydrothermal treatment is 2 times, and the conditions of each hydrothermal treatment are as follows: the temperature is 620°C, under 100% water vapor treatment conditions, the treatment time is 6 hours. The water vapor treatment process is a flowing water vapor treatment. Then use 0.3 mol / L citric acid at a solid-liquid ratio of 1.0g:6.0mL at 80°C for 4 hours.
[0058] Example 2
[0059] (1) Preparation of Fe-containing Y molecular sieve guide body: The first Fe source is ferric chloride, the first aluminum source is sodium aluminate, the first alkali source is NaOH, and the first silicon source is silica sol. After the first aluminum source and the first alkali source are mixed and dissolved in water, the first Fe source and the first silicon source are added in sequence, mixed evenly, and allowed to stand to obtain the Fe-containing Y molecular sieve guide body. Among them, the first aluminum source is calculated as Al2O3, the first alkali source is calculated as NaOH, the first Fe source is calculated as Fe2O3, and the first silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the Y molecular sieve guide body is 1:28:0.6:16:340. The standing temperature is 40°C and the standing time is 24 hours.
[0060] (2) Prepare a matrix mixed solution; in the matrix mixed solution, the second Fe source is ferric sulfate, the second aluminum source is sodium aluminate and aluminum sulfate (the molar ratio of sodium aluminate and aluminum sulfate is 1:0.53), the second alkali source is selected from NaOH, and the second silicon source is water glass. In the matrix solution, the second aluminum source is calculated as Al2O3, the second alkali source is calculated as NaOH, the second Fe source is calculated as Fe2O3, and the second silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the feed is 1:4.8:0.4:6.2:180. The amount of the Fe-containing Y molecular sieve guide added in step (1) is 15.0% of the total mass of the matrix mixed solution. The second Fe source is dissolved in the second aluminum source sodium aluminate aqueous solution, wherein the mass content of Fe (in terms of oxide) is 8.0%. After ultrasonic treatment (frequency 35kHz) for 3 hours and a standing process, the standing time is 18 hours, and the second Fe source feed is obtained. The second alkali source and the second silicon source are mixed with the remaining water, and then the guide body obtained in step (1), the second Fe source feed, and the second aluminum source aluminum sulfate are added in sequence and mixed evenly to obtain a gel.
[0061] (3) The gel obtained in step (2) is crystallized; the crystallization adopts three-stage temperature rising crystallization, the first stage crystallization temperature is 30° C., the second stage crystallization temperature is 65° C., and the third stage crystallization temperature is 100° C. The crystallization time of each stage is 18 hours.
[0062] (4) The crystallized product obtained in step (3) is subjected to ammonium exchange, hydrothermal treatment, and acid washing to obtain USY molecular sieve. The ammonium exchange is a conventional ammonium exchange. The ammonium salt used is ammonium nitrate, wherein the concentration of the ammonium salt solution is 0.1 mol / L and the pH value is 6.8. The ammonium exchange temperature is 60°C and the number of ammonium exchanges is 2 times. The solid-liquid volume ratio of each ammonium exchange is 1:10, and the treatment time of each ammonium exchange is 6 hours. The hydrothermal treatment is performed twice, and the conditions of each hydrothermal treatment are as follows: the temperature is 620°C, the treatment time is 6 hours under 100% water vapor treatment conditions. The water vapor treatment process is a flowing water vapor treatment. Then, 0.3 mol / L citric acid is used at a solid-liquid ratio of 1.0 g:6.0 mL at 70°C for 5 hours.
[0063] Example 3
[0064] (1) Preparation of Fe-containing Y molecular sieve guide body: The first Fe source is ferric chloride, the first aluminum source is sodium aluminate, the first alkali source is NaOH, and the first silicon source is silica sol. After the first aluminum source and the first alkali source are mixed and dissolved in water, the first Fe source and the first silicon source are added in sequence, mixed evenly, and allowed to stand to obtain the Fe-containing Y molecular sieve guide body. Among them, the first aluminum source is calculated as Al2O3, the first alkali source is calculated as NaOH, the first Fe source is calculated as Fe2O3, and the first silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the feed is 1:30:0.5:15:300. The standing temperature is 25°C and the standing time is 22 hours.
[0065] (2) Prepare a matrix mixed solution; in the matrix mixed solution, the second Fe source is ferric chloride, the second aluminum source is sodium aluminate and aluminum sulfate (the molar ratio of sodium aluminate and aluminum sulfate is 1:0.50), the second alkali source is selected from NaOH, and the second silicon source is water glass. In the matrix solution, the second aluminum source is calculated as Al2O3, the second alkali source is calculated as NaOH, the second Fe source is calculated as Fe2O3, and the second silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the feed is 1:5.0:0.43:5.5:140. The amount of the Fe-containing Y molecular sieve guide added in step (1) is 10.0% of the total mass of the matrix mixed solution. The second Fe source is dissolved in the second aluminum source sodium aluminate aqueous solution, wherein the mass content of Fe is 10.0%, and after ultrasonic treatment (frequency 35kHz) for 4 hours and a standing process, the standing time is 18 hours, to obtain the second Fe source feed. The second alkali source and the second silicon source are mixed with the remaining water, and then the guide body obtained in step (1), the second Fe source feed, and the second aluminum source aluminum sulfate are added in sequence and mixed evenly to obtain a gel.
[0066] (3) The gel obtained in step (2) is crystallized; the crystallization adopts three-stage temperature rising crystallization, the first stage crystallization temperature is 30° C., the second stage crystallization temperature is 65° C., and the third stage crystallization temperature is 100° C. The crystallization time of each stage is 18 hours.
[0067] (4) The crystallized product obtained in step (3) is subjected to ammonium exchange, hydrothermal treatment, and acid washing to obtain USY molecular sieve. The ammonium exchange is a conventional ammonium exchange. The ammonium salt used is ammonium nitrate, wherein the concentration of the ammonium salt solution is 0.1 mol / L and the pH value is 6.8. The ammonium exchange temperature is 60°C and the number of ammonium exchanges is 2 times. The solid-liquid volume ratio of each ammonium exchange is 1:10, and the treatment time of each ammonium exchange is 6 hours. The hydrothermal treatment is performed twice, and the conditions of each hydrothermal treatment are as follows: the temperature is 620°C, the treatment time is 6 hours under 100% water vapor treatment conditions. The water vapor treatment process is a flowing water vapor treatment. Then, 0.3 mol / L citric acid is used at a solid-liquid ratio of 1.0 g:6.0 mL at 60°C for 3 hours.
[0068] Example 4
[0069] (1) Preparation of Fe-containing Y molecular sieve guide body: The first Fe source is ferric chloride, the first aluminum source is sodium aluminate, the first alkali source is NaOH, and the first silicon source is silica sol. After the first aluminum source and the first alkali source are mixed and dissolved in water, the first Fe source and the first silicon source are added in sequence, mixed evenly, and allowed to stand to obtain the Fe-containing Y molecular sieve guide body. Among them, the first aluminum source is calculated as Al2O3, the first alkali source is calculated as NaOH, the first Fe source is calculated as Fe2O3, and the first silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the feed is 1:30:0.5:15:300. The standing temperature is 25°C and the standing time is 22 hours.
[0070] (2) Prepare a matrix mixed solution; in the matrix mixed solution, the second Fe source is ferric chloride, the second aluminum source is sodium aluminate and aluminum sulfate (the molar ratio of sodium aluminate and aluminum sulfate is 1:0.5), the second alkali source is selected from NaOH, and the second silicon source is water glass. In the matrix solution, the second aluminum source is calculated as Al2O3, the second alkali source is calculated as NaOH, the second Fe source is calculated as Fe2O3, and the second silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the feed is 1:5.2:0.45:5.6:120. The amount of the Fe-containing Y molecular sieve guide added in step (1) is 15.0% of the total mass of the matrix mixed solution. The second Fe source is dissolved in the second aluminum source aluminum sulfate aqueous solution, wherein the mass content of Fe is 12.0%, and after ultrasonic treatment (frequency 40kHz) for 1 hour and a standing process, the standing time is 18 hours, to obtain the second Fe source feed. The second alkali source and the second silicon source are mixed with the remaining water, and then the guide body obtained in step (1), the second Fe source feed, and the second aluminum source sodium aluminate are added in sequence and mixed evenly to obtain a gel.
[0071] (3) The gel obtained in step (2) is crystallized; the crystallization adopts three-stage temperature rising crystallization, the first stage crystallization temperature is 40° C., the second stage crystallization temperature is 75° C., and the third stage crystallization temperature is 110° C. The crystallization time of each stage is 12 hours.
[0072] (4) The crystallized product obtained in step (3) is subjected to ammonium exchange, hydrothermal treatment, and acid washing to obtain USY molecular sieve. The ammonium exchange is a conventional ammonium exchange. The ammonium salt used is ammonium nitrate, wherein the concentration of the ammonium salt solution is 0.1 mol / L and the pH value is 6.8. The ammonium exchange temperature is 60°C and the number of ammonium exchanges is 2 times. The solid-liquid volume ratio of each ammonium exchange is 1:10, and the treatment time of each ammonium exchange is 6 hours. The hydrothermal treatment is performed twice, and the conditions of each hydrothermal treatment are as follows: the temperature is 620°C, the treatment time is 6 hours under 100% water vapor treatment conditions. The water vapor treatment process is a flowing water vapor treatment. Then, 0.3 mol / L oxalic acid is used at a solid-liquid ratio of 1.0 g:6.0 mL at 60°C for 4 hours.
[0073] Example 5
[0074] (1) Preparation of Fe-containing Y molecular sieve guide body: The first Fe source is ferric chloride, the first aluminum source is sodium aluminate, the first alkali source is NaOH, and the first silicon source is silica sol. After the first aluminum source and the first alkali source are mixed and dissolved in water, the first Fe source and the first silicon source are added in sequence, mixed evenly, and allowed to stand to obtain the Fe-containing Y molecular sieve guide body. Among them, the first aluminum source is calculated as Al2O3, the first alkali source is calculated as NaOH, the first Fe source is calculated as Fe2O3, and the first silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the feed is 1:30:0.5:15:300. The standing temperature is 25°C and the standing time is 22 hours.
[0075] (2) Prepare a matrix mixed solution; in the matrix mixed solution, the second Fe source is ferric chloride, the second aluminum source is sodium aluminate and aluminum sulfate (the molar ratio of sodium aluminate and aluminum sulfate is 1:0.52), the second alkali source is selected from NaOH, and the second silicon source is water glass. In the matrix solution, the second aluminum source is calculated as Al2O3, the second alkali source is calculated as NaOH, the second Fe source is calculated as Fe2O3, and the second silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the feed is 1:5.2:0.45:5.6:120. The amount of the Fe-containing Y molecular sieve guide added in step (1) is 15.0% of the total mass of the matrix mixed solution. The second Fe source is dissolved in the second silicon source water glass solution, wherein the mass content of Fe is 4.0%. After ultrasonic treatment (frequency 20kHz) for 4 hours and a standing process, the standing time is 18 hours, to obtain the second Fe source feed. The second alkali source is mixed with the remaining water and then the guide obtained in step (1), the second Fe source feed, the second aluminum source sodium aluminate, and the second aluminum source aluminum sulfate are added in sequence and mixed to obtain a gel.
[0076] (3) The gel obtained in step (2) is crystallized; the crystallization adopts three-stage temperature rising crystallization, the first stage crystallization temperature is 30° C., the second stage crystallization temperature is 65° C., and the third stage crystallization temperature is 100° C. The crystallization time of each stage is 18 hours.
[0077] (4) The crystallized product obtained in step (3) is subjected to ammonium exchange, hydrothermal treatment, and acid washing to obtain USY molecular sieve. The ammonium exchange is a conventional ammonium exchange. The ammonium salt used is ammonium chloride, wherein the concentration of the ammonium salt solution is 0.1 mol / L and the pH value is 5.2. The ammonium exchange temperature is 80°C and the number of ammonium exchanges is 2 times. The solid-liquid volume ratio of each ammonium exchange is 1:10, and the treatment time of each ammonium exchange is 4 hours. The hydrothermal treatment is performed twice, and the conditions of each hydrothermal treatment are as follows: the temperature is 600°C, the treatment time is 4 hours under 100% water vapor treatment conditions. The water vapor treatment process is a flowing water vapor treatment. Then, 0.3 mol / L citric acid is used at a solid-liquid ratio of 1.0 g:6.0 mL at 50°C for 6 hours.
[0078] Example 6
[0079] (1) Preparation of Fe-containing Y molecular sieve guide body: The first Fe source is ferric chloride, the first aluminum source is sodium aluminate, the first alkali source is NaOH, and the first silicon source is silica sol. After the first aluminum source and the first alkali source are mixed and dissolved in water, the first Fe source and the first silicon source are added in sequence, mixed evenly, and allowed to stand to obtain the Fe-containing Y molecular sieve guide body. Among them, the first aluminum source is calculated as Al2O3, the first alkali source is calculated as NaOH, the first Fe source is calculated as Fe2O3, and the first silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the feed is 1:30:0.50:15:300. The standing temperature is 25°C and the standing time is 22 hours.
[0080] (2) Prepare a matrix mixed solution; in the matrix mixed solution, the second Fe source is ferric chloride, the second aluminum source is sodium aluminate and aluminum sulfate (the molar ratio of sodium aluminate and aluminum sulfate is 1:0.52), the second alkali source is selected from NaOH, and the second silicon source is water glass. In the matrix solution, the second aluminum source is calculated as Al2O3, the second alkali source is calculated as NaOH, the second Fe source is calculated as Fe2O3, and the second silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O in the feed is 1:5.2:0.45:5.6:120. The amount of the Fe-containing Y molecular sieve guide added in step (1) is 15.0% of the total mass of the matrix mixed solution. The second Fe source is dissolved in water, wherein the mass content of Fe (in terms of oxide) is 6.0%, and after ultrasonic treatment (frequency 25kHz) for 4 hours and a standing process, the standing time is 18 hours, to obtain the second Fe source feed. The second alkali source and the second silicon source are mixed with the remaining water, and then the guide body obtained in step (1), the second Fe source feed, the second aluminum source sodium aluminate, and the second aluminum source aluminum sulfate are added in sequence, and mixed evenly to obtain a gel.
[0081] (3) The gel obtained in step (2) is crystallized; the crystallization adopts three-stage temperature rising crystallization, the first stage crystallization temperature is 30° C., the second stage crystallization temperature is 65° C., and the third stage crystallization temperature is 100° C. The crystallization time of each stage is 18 hours.
[0082] (4) The crystallized product obtained in step (3) is subjected to ammonium exchange, hydrothermal treatment, and acid washing to obtain USY molecular sieve. The ammonium exchange is a conventional ammonium exchange. The ammonium salt used is ammonium nitrate, wherein the concentration of the ammonium salt solution is 0.1 mol / L and the pH value is 6.8. The ammonium exchange temperature is 60°C and the number of ammonium exchanges is 2 times. The solid-liquid volume ratio of each ammonium exchange is 1:10, and the treatment time of each ammonium exchange is 6 hours. The hydrothermal treatment is performed twice, and the conditions of each hydrothermal treatment are as follows: the temperature is 620°C, the treatment time is 6 hours under 100% water vapor treatment conditions. The water vapor treatment process is a flowing water vapor treatment. Then, 0.3 mol / L citric acid is used at a solid-liquid ratio of 1.0 g:6.0 mL at 80°C for 4 hours.
[0083] Example 7
[0084] Compared with Example 1, the difference is that the water vapor treatment process in step (4) is a closed treatment.
[0085] Comparative Example 1
[0086] Compared with Example 1, the difference is that the first Fe source is not added to the Y molecular sieve guide body prepared in step (1), but the first aluminum source, the first alkali source, the first silicon source and water are mixed and allowed to stand to obtain the Y molecular sieve guide body.
[0087] Comparative Example 2
[0088] Compared with Example 1, the difference is that the amount of the Fe-containing Y molecular sieve guide added to the matrix mixed solution in step (2) is 8.0% of the total material mass of the matrix solution.
[0089] Comparative Example 3
[0090] Compared with Example 1, the difference is that in step (3), a three-stage temperature increase crystallization process is not adopted, but the crystallization temperature is 65° C. for 54 hours.
[0091] Application Examples
[0092] The present invention provides the use of each example of molecular sieve in a flexible hydrocracking catalyst: the molecular sieve, aluminum oxide, molybdenum oxide, tungsten oxide, nickel oxide and sesbania powder prepared in each example are uniformly mixed in a certain proportion, an inorganic acid is added as a binder, the powder is uniformly rolled and formed, and after drying at 120° C. for 4 hours and calcining at 500° C. for 6 hours, a hydrocracking catalyst is obtained, the properties of which are shown in Table 2, and the catalyst numbers are A-1 to A-7 and D-1 to D-3, respectively.
[0093] Evaluation of the catalyst: The above-prepared catalysts were evaluated on a 200mL small hydrogenation unit, and the catalysts were pre-sulfurized before the reaction. The properties of the feedstock oil used in the evaluation test are shown in Table 3. The process conditions and reaction performance results of the evaluation test are shown in Tables 4 and 5. When evaluating the flexible hydrocracking catalyst, the feedstock oil passed through two beds of the hydrorefining catalyst and the above-prepared flexible hydrocracking catalyst in sequence. Among them, when passing through the hydrorefining catalyst bed, the organic nitrogen content in the feedstock oil was controlled to be less than 10ppm.
[0094] Table 1 Properties of the molecular sieves prepared in each example
[0095]
[0096] Table 2 Composition of hydrocracking catalyst
[0097]
[0098]
[0099] Table 3 Properties of the feedstock oil used in the evaluation test
[0100] <![CDATA[Density (20 °C), g / cm 3 > 0.89 Distillation range, ℃ IBP / EBP 355 / 511 Pour point, ℃ 32 Carbon residue, wt% 0.21 S, wt% 1.4 N, wt% 0.16
[0101] Table 4 Process conditions and reaction performance results of the catalyst evaluation test of the present invention
[0102]
[0103] Table 5 Comparison of process conditions and reaction performance results of catalyst evaluation test
[0104]
[0105] It can be seen from Table 4 and Table 5 that when the conversion rate of the controlled reaction is the same, the reaction activity and selectivity of the target product using the catalyst of the present invention are better.
[0106] The embodiments of the present invention are only detailed descriptions of the technical solutions of the present invention, but the present invention is not limited to the above embodiments, that is, the present invention can be implemented without relying on the steps described in the above embodiments. In summary, any improvements made by those skilled in the art to the present invention, including replacement of the raw materials and additives described in the present invention, selection of specific implementation methods, etc., all belong to the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing an ultrastable Y-type molecular sieve, comprising the following steps: (1) mixing a first aluminum source, a first alkali source, a first Fe source, a first silicon source and water to obtain a Fe-containing Y molecular sieve guide; (2) mixing a second aluminum source, a second silicon source, a second Fe source, a second alkali source, water and the guide body of step (1) to obtain a gel; (3) crystallizing the gel of step (2); (4) The crystallized product obtained in step (3) is subjected to ammonium exchange, hydrothermal treatment, and acid washing to obtain an ultra-stable Y-type molecular sieve.
2. The preparation method according to claim 1, characterized in that: In step (1), a first aluminum source, a first alkali source, a first Fe source, a first silicon source and water are mixed and allowed to stand to obtain a Fe-containing Y molecular sieve guide. Preferably, the standing temperature is 10 to 50° C. and the standing time is 15 to 35 hours.
3. The preparation method according to claim 1 or 2, characterized in that: The first aluminum source is calculated as Al2O3, the first alkali source is calculated as NaOH, the first Fe source is calculated as Fe2O3, and the first silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O is 1:(11~42):(0.05~10.0):(5~25):(180~450), preferably 1:(15~35):(0.05~8.0):(5~18):(180~400).
4. The preparation method according to claim 1 or 2, characterized in that: In step (2), the second aluminum source is calculated as Al2O3, the second alkali source is calculated as NaOH, the second Fe source is calculated as Fe2O3, and the second silicon source is calculated as SiO2. The molar ratio of Al2O3:NaOH:Fe2O3:SiO2:H2O is 1:(1.5~15.0):(0.05~12.0):(1.5~12.0):(80~400), preferably 1:(1.5~10.0):(0.05~8.0):(1.5~8.0):(80~350).
5. The preparation method according to claim 1, characterized in that: In step (2), the second Fe source is introduced into the reaction system in the form of a second Fe source feed, and the second Fe source feed is preferably prepared in at least one of the following ways: a. at least part of the second Fe source and at least part of the second silicon source are used to form a second Fe source feed, b. at least part of the second Fe source and at least part of the second aluminum source are used to form a second Fe source feed, c. preparing a second Fe source feed with at least part of the second Fe source, at least part of the second aluminum source and at least part of the second silicon source; Preferably, the second Fe source feed is subjected to ultrasonic treatment and then to a standing process (preferably, the standing time is 1 to 48 hours, preferably 12 to 24 hours) before being introduced into the reaction system.
6. The preparation method according to claim 5, characterized in that: In the second Fe source feed, the mass content of Fe is 0.5% to 12.0% in terms of oxide; And / or, the ultrasonic treatment conditions are as follows: temperature 20-80° C., preferably 20-60° C., ultrasonic frequency 20-50 kHz, time 1-8 h, preferably 1-4 h.
7. The preparation method according to claim 1, characterized in that: In step (2), the amount of Fe-containing Y molecular sieve guide added is 10.0% to 45.0% of the total material mass of the matrix mixed solution, and the matrix mixed solution is a second aluminum source, a second silicon source, a second Fe source, a second alkali source and water.
8. The preparation method according to claim 1, characterized in that: The first Fe source or the second Fe source is independently selected from at least one of ferric chloride, ferric sulfate, and ferric nitrate; the first aluminum source or the second aluminum source is independently selected from at least one of sodium aluminate and aluminum sulfate; the first alkali source or the second alkali source is independently selected from at least one of NaOH and KOH, and the first silicon source or the second silicon source is independently selected from at least one of silica sol and water glass.
9. The preparation method according to claim 1, characterized in that: The crystallization adopts three-stage temperature rising crystallization, the first-stage crystallization temperature is 30-40°C, the second-stage crystallization temperature is 30-35°C higher than the first-stage temperature, the third-stage crystallization temperature is 25-50°C higher than the second-stage temperature, and the highest temperature does not exceed 110°C; the crystallization time of each stage is 12-36 hours, preferably 15-24 hours.
10. The preparation method according to claim 1, characterized in that: In step (4), the hydrothermal treatment is performed 1 to 3 times, and the conditions for each hydrothermal treatment are as follows: the temperature is 500 to 650° C., the treatment time is 1 to 6 hours under 100% water vapor treatment conditions; Preferably, the water vapor treatment is a closed water vapor treatment or a flowing water vapor treatment, preferably a flowing water vapor treatment.
11. The preparation method according to claim 1, characterized in that: In step (4), the acid in the acid solution used for pickling treatment is selected from at least one of citric acid, oxalic acid, and tartaric acid, and the concentration of the acid solution is 0.1 to 3.0 mol / L; And / or, the solid-liquid ratio in the pickling treatment is 1.0 g: 5.0-20.0 mL, the temperature of the pickling treatment is 30.0-95.0° C., and the time of the pickling treatment is 1-6 hours.
12. An ultrastable Y-type molecular sieve prepared by any one of the methods of claims 1-11.
13. The molecular sieve according to claim 12, characterized in that: In the molecular sieve, the SiO2 / Al2O3 molar ratio is 7.0-27.5, preferably 17.0-20.0; and / or the mesopore volume accounts for 35%-55% of the total pore volume of the molecular sieve, preferably 38%-55%; and / or the specific surface area is 550-655m 2 / g, pore volume is 0.42-0.48 mL / g; and / or, the average size of the crystallites is 0.4-1.2 μm, preferably 400-600 nm; and / or, the unit cell constant is 14. Use of the ultrastable Y-type molecular sieve according to any one of claims 12 to 13 in a hydrocracking catalyst.
Citation Information
Patent Citations
Preparation method for small-grain Y type molecular sieve
CN104828839A
Method for improving Y-shaped molecular sieve water heat stability by employing cage heteroatom
CN101134576A
Hydrocracking catalyst
CN102091649A
Preparation method of high silica-alumina ratio Y type zeolite rich in secondary pores
CN103539151A
Method for synthesis of high silica-alumina ratio ultrafine NaY molecular sieve
CN104743572A